Nursery Rearing of Catla (Catla catla) Under Different Dietary Protein and Fertilization Levels - J.K., Manissery; D., Krishnamurthy; B., Gangadhar; M.C., Nandeesha (Fishery Technology, 2025)
Catla (Catla catla) spawn were stocked at 5 million/ha in a commercial fish seed farm. Cow dung at the rate of 13,000 (Tl), 15,000 (T2) and 18,500 kg/ha (T3) were applied in split doses during the experimental period of 21 days. Finely powdered groundnut cake-rice bran mixture (1:1) served as control diet (A). Experimental diets were formulated by incorporating fish meal at 10 (B), 24 (C) and 38% (D) level in the control diet. All the diets were tested at each level of fertilization and fed at equivalent, 3 times and 4 times the initial body weight for the first 5, next 10 and rest of the days respectively. Irrespective of the diet given, increased growth and survival of catla and increased weight of plankton were recorded with increase in fertilization rate. The highest average length and weight gain were observed in fish fed diet C with 35% protein. The overall survival was the highest in T3 and lowest in tl. Fish meal based diet with 35% protein was found to be ideal for the nursery rearing of catla in fertilized ponds to obtain higher growth and survival.